Mengejar dan Melupakan Kebahagiaan dalam Perspektif Zhuangzi - Agustinus Lie (Sekolah Tinggi Widya Sasana, 2021)
The search of happiness often misleads people to objectify happiness itself. In Zhuangzi's philosophical view, happiness is a state of continuous flow in an endless process. If one is immersed in the process, happiness itself will appear in the state of oblivion. He will forget his starting point, flow like the wind, and will not pay attention to the end of the process or the set goal. He will join in the process, forget about himself, and forget everything around him. Through oblivion, one will be free to roam without anyone getting in his way. Zhuangzi uses humorous and lively stories to lead every reader to seek and afterward forget happiness. A paradoxical condition arises here. Forgetting happiness is a way to reach deeper happiness